INFORMATION EXTRACTION FROM LAPAN SATELLITE AIS DATABASE FOR SHIP CLASSIFICATION IN THE INDONESIAN TERRITORIAL WATERS - Nugroho, Muazam; Ferdiansyah, Nurrochman; Rahayu, Dicka Ariptian; Permala, Rizki; Hakim, Patria Rachman; Hasbi, Wahyudi (BRIN Publishing, 2021)
Automatic Identification System (AIS) is a system used to monitor ship activity by sending ship information via Very High Frequency (VHF) waves. Information sent by ships around the world is recorded by AIS receivers carried by the LAPAN-A2 and LAPAN-A3 satellites along their orbital trajectories. The AIS data recorded by the satellite will then be acquired and stored at the LAPAN earth station. This study focuses on extracting information from the LAPAN satellite AIS database to obtain information on the number of vessels based on a unique Maritime Mobile Service Identity (MMSI) grouped according to the type of vessel entering Indonesian waters with coordinates 95BT / 141BT, -11LS / 6LU every month. in the period January to December 2019. The results of extracting the information are in the form of the number of ships based on unique MMSI which are grouped according to the type of ship in the territory of Indonesia with that region and time period